Loving Monsters: The Curious Case of Patricia Piccinini’s Posthuman Offspring - Biscaia, Maria Sofia Pimentel (Nordlit, 2019)
Patricia Piccinini’s work has been described as disquieting, compelling and grotesque. Other adjectives often used include disturbing, visceral, monstrous, chimerical but also cute and beautiful. The reason for the encounter of such descriptions which are typically found in separate realms is precisely that Piccinini seeks to fracture unitarian conceptualisations of humanness as she strives to materially debate issues of posthuman ethics. Her concerns relate to issues of breeding, mutation, biotechnology, motherhood/childhood, eco-philosophy and speciesism. In this paper, I will set off from the works of Donna Haraway and Rosi Braidotti to discuss Piccinini’s posthuman aesthetics and ethics. I propose to investigate the affirmative posthuman predicament which she has creatively designed for the art gallery space, reflecting the technocultural fabrications of our natureculture continuum. I will focus my attention on three posthuman propositions as they relate to the discourses of motherhood and reproduction: the cyborgian realities of the human and the animal; the organism and the machine; as well as the human, the animal and the vegetable. Piccinini’s reconfigurations are created into a world of tenderness and imbued with an ethics of care as she, unlike Victor Frankenstein, aims to love her creatures.